The effect of curvature on the stress concentrations around holes in shells - Houghton, D. S.; Rothwell, A. (College of Aeronautics, 1962)
An experimental investigation has been carried out to investigate the effect of curvature on the stress concentrations around holes in shell structures. Two methods have been employed: - (I) Araldite cylinders, containing holes of various shapes, subjected to axial tension, internal pressure and torsion were examined by the photoelastic frozen stress technique. (2) Aluminium alloy curved panels and hemispheres were used in conjunction with miniature electrical strain gauges. The results are compared with the theoretical solutions and suggest that the curvature effect can be significant, particularly for the case of shear or biaxial loading.